Active forum topics
- Inverse Trigo
- General Solution of $y' = x \, \ln x$
- engineering economics: construct the cash flow diagram
- Eliminate the Arbitrary Constants
- Law of cosines
- Maxima and minima (trapezoidal gutter)
- Special products and factoring
- Integration of 4x^2/csc^3x√sinxcosx dx
- application of minima and maxima
- Sight Distance of Vertical Parabolic Curve
New forum topics
- Inverse Trigo
- General Solution of $y' = x \, \ln x$
- engineering economics: construct the cash flow diagram
- Integration of 4x^2/csc^3x√sinxcosx dx
- Maxima and minima (trapezoidal gutter)
- Special products and factoring
- Newton's Law of Cooling
- Law of cosines
- Can you help me po to solve this?
- Eliminate the Arbitrary Constants
Recent comments
- Yes.1 week 2 days ago
- Sir what if we want to find…1 week 2 days ago
- Hello po! Question lang po…3 weeks 6 days ago
- 400000=120[14π(D2−10000)]
(…2 months ago - Use integration by parts for…2 months 4 weeks ago
- need answer2 months 4 weeks ago
- Yes you are absolutely right…3 months ago
- I think what is ask is the…3 months ago
- $\cos \theta = \dfrac{2}{…3 months ago
- Why did you use (1/SQ root 5…3 months ago
The center of the circle is $
The center of the circle is $(a, 0)$ and the fixed radius is, say, $r$.
Thus the equation of the circle is $(x-a)^2+y^2 = r^2$. Since $a$ is the arbitrary constant here, get the derivative once.
\begin{eqnarray*}
(x-a)^2+y^2 &=& r^2\\
2(x-a) + 2y y' &=& 0\\
(x-a) + yy' &=& 0\\
x-a &=& -yy'
\end{eqnarray*}
Then substitute to the original equation.
\begin{eqnarray*}
(x-a)^2 + y^2 &=& r^2\\
(yy')^2 + y^2 &=& r^2\\
y^2((y')^2 + 1) &=& r^2
\end{eqnarray*}
Thus the differential equation is $\boxed{y^2((y')^2 + 1) = r^2}$